2008
DOI: 10.1016/j.canlet.2008.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Multi-targeted therapy of cancer by genistein

Abstract: Soy isoflavones have been identified as dietary components having an important role in reducing the incidence of breast and prostate cancers in Asian countries. Genistein, the predominant isoflavone found in soy products, has been shown to inhibit the carcinogenesis in animal models. There is a growing body of experimental evidence showing that the inhibition of human cancer cell growth by genisteinis mediated via the modulation of genes that are related to the control of cell cycle and apoptosis. It has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
383
0
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 560 publications
(405 citation statements)
references
References 130 publications
(85 reference statements)
9
383
0
5
Order By: Relevance
“…We found that HOTAIR and miR-141 expression are inversely correlated in renal carcinoma cells. Genistein has potent biological activity, regulates several signaling pathways in cancer cells, and promotes cancer cell death (29,30,50,51), and we have found that genistein regulates miRNAs (33,(52)(53)(54). We also found that genistein decreases HOTAIR expression while stimulating miR-141 expression, showing an inverse effect.…”
Section: Discussionmentioning
confidence: 53%
“…We found that HOTAIR and miR-141 expression are inversely correlated in renal carcinoma cells. Genistein has potent biological activity, regulates several signaling pathways in cancer cells, and promotes cancer cell death (29,30,50,51), and we have found that genistein regulates miRNAs (33,(52)(53)(54). We also found that genistein decreases HOTAIR expression while stimulating miR-141 expression, showing an inverse effect.…”
Section: Discussionmentioning
confidence: 53%
“…7,8 The 2 flavonoid subclasses, anthocyanidins and isoflavonoids, that showed a protective effect in our study have various anticarcinogenic properties and are currently being tested in clinical trials. 20,21 Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Ϫ/Ϫ Hepatocytes-In addition to its direct effect on tyrosine kinases, several reports have related genisteinproapototic effects with NF-B pathway inhibition, which also can counteract TGF-␤ signaling (12,25). For this reason, we decided to investigate a possible implication of NF-B in our model.…”
Section: Activation Of Nf-b Pathway Is Responsible For Tgf-␤ Resistanmentioning
confidence: 99%